How Many Lymph Nodes Are Enough? Assessing the Adequacy of Lymph Node Yield for Papillary Thyroid Cancer - Robinson, Timothy J. (J Clin Oncol, 2016)
PURPOSE: Patients who undergo surgery for papillary thyroid cancer with only a limited lymph node examination are thought to be at risk for potentially harboring occult disease. However, this risk has not been objectively quantified and may have implications for subsequent management and surveillance. METHODS: Data from the National Cancer Database (1998 to 2012) were used to characterize the distribution of nodal positivity of adult patients diagnosed with localized ≥ 1-cm papillary thyroid cancer who underwent thyroidectomy with one or more lymph nodes (LNs) examined. A β-binomial distribution was used to estimate the probability of occult nodal disease as a function of total number of LNs examined and pathologic tumor stage. RESULTS: A total of 78,724 patients met study criteria; 38,653 patients had node-positive disease. The probability of falsely identifying a patient as node negative was estimated to be 53% for patients with a single node examined and decreased to less than 10% when more than six LNs were examined. To rule out occult nodal disease with 90% confidence, six, nine, and 18 nodes would need to be examined for patients with T1b, T2, and T3 disease, respectively. Sensitivity analyses limited to patients likely undergoing prophylactic central neck dissection resulted in three, four, and eight nodes needed to provide comparable adequacy of LN evaluation. CONCLUSION: To our knowledge, our study provides the first empirically based estimates of occult nodal disease risk in patients after surgery for papillary thyroid cancer as a function of primary tumor stage and number of LNs examined. Our estimates provide an objective guideline for evaluating adequacy of LN yield for surgeons and pathologists in the treatment of papillary thyroid cancer, and especially intermediate-risk disease, for which use of adjuvant radioactive iodine and surveillance intensity are not currently standardized.